Public financing of healthcare services - Agnieszka Bem (e-Finanse: Financial Internet Quarterly, 2013)
Healthcare in Poland is mainly financed by public sector entities, among them the National Health Fund (NFZ), state budget and local government budgets. The task of the National Health Fund, as the main payer in the system, is chiefly currently financing the services. The state budget plays a complementary role in the system, and finances selected groups of services, health insurance premiums and investments in healthcare infrastructure. The basic role of the local governments is to ensure access to the services, mostly by performing ownership functions towards healthcare institutions.
Keywords: I11; I15; I18; 330; healthcare financing; public funds; Poland